Perhitungan Overall Equipment Effectiveness (OEE) di PT. ABC - Adrian, Giovanni; Octavia, Tanti (Jurnal Titra, 2015)
PT. ABC would like to know the effectiveness of each production machines. The company wants to calculate the effectiveness of each production machines everyday, so that can be evaluated monthly. Therefore, this project is conducted to design the tools for calculating the level of machines effectiveness using Overall Equipment Effectiveness (OEE). Result of data processing shown that the average of effectiveness for all moulding machines is 43%. The quality indicatorÂ became one of the causes of the low value of the average OEE for moulding machines. The ways to increase quality indicator are to make an additional tools on bandsaw machine, grouping the timber at unstacking on KD process, and to increase the operatorâs utility when downtime occurs. After implementating, the OEEÂ becomes 45%. The tools for calculating the OEE are also designed for the company. Those are moulding production data form, OEE calculator, and OEE calculation module.